Feed Additives for Aquaculture and Aquarium Culture - Barata, Eduardo N. (2011)
The presente invention refers of feed additives for aquaculture and aquarium culture. These additives comprise the amino acid, 1-methyl-L-tryptophane, or its isomers with the objective of improving the attractiveness of feeds used in aquaculture and aquaria for fish, as well as other aquatic organisms, under culture conditions. Therefore, this invention has applications in the agriculture-food industry.